Wind Energy Integration into the SAARC Region: A Comprehensive Review of Optimal Wind Sites for a Sustainable Super Smart Grid - Basit Ahmad; Dr. Saqib Ali; Maryam Muneer; Arooj Fatima; Naveed Abbas (Dialogue Social Science Review (DSSR), 2025)
Approximately 25% of global population residues in South Asia. The power generation of these population relies heavily on Non-renewable energy sources, resulting in large greenhouse gases emission into the atmosphere. In order to protect the environment, the SAARC countries has decided to construct an extremely intelligent smart grid to share electricity across SAARC nations based on sustainable energy sources but the ability of these nations to develop such a super power grid is unclear because of the absence of Effective strategic assessment and an insufficient information about the potential sites of RERs. This review delivers an extensive impression of the wind energy and identify the exact locations of high wind potential within the SAARC region. We use wind speed readings, satellite data, and geographic information systems (GIS) to give an in-depth investigation of wind patterns and yearly changes in wind resources across member countries. The research further investigates numerous socioeconomic factors affecting wind energy development and discussing obstacles like infrastructure limits, financial difficulties, and laws and regulations. Successful case of public-private alliances and worldwide collaboration are showcase to illustrate pathways for growth. The result of this research provides different perspectives to policy makers and practitioners for strategic decisions regarding SAARC super smart grid.